B cell‐intrinsic MyD88 signaling controls IFN‐γ‐mediated early IgG2c class switching in mice in response to a particulate adjuvant. Issue 9 (21st May 2019) - Lee, Michelle Sue Jann; Natsume‐Kitatani, Yayoi; Temizoz, Burcu; Fujita, Yukiko; Konishi, Aki; Matsuda, Kyoko; Igari, Yoshikatsu; Tsukui, Toshihiro; Kobiyama, Kouji; Kuroda, Etsushi; Onishi, Motoyasu; Marichal, Thomas; et al.
Abstract: Adjuvants improve the potency of vaccines, but the modes of action (MOAs) of most adjuvants are largely unknown. TLR‐dependent and ‐independent innate immune signaling through the adaptor molecule MyD88 has been shown to be pivotal to the effects of most adjuvants; however, MyD88's involvement in the TLR‐independent MOAs of adjuvants is poorly understood. Here, using the T‐dependent antigen NIPOVA and a unique particulate adjuvant called synthetic hemozoin (sHZ), we show that MyD88 is required for early GC formation and enhanced antibody class‐switch recombination (CSR) in mice. Using cell‐type‐specific MyD88 KO mice, we found that IgG2c class switching, but not IgG1 class switching, was controlled by B cell‐intrinsic MyD88 signaling. Notably, IFN‐γ produced by various cells including T cells, NK cells, and dendritic cells was the primary cytokine for IgG2c CSR and B‐cell intrinsic MyD88 is required for IFN‐γ production. Moreover, IFN‐γ receptor (IFNγR) deficiency abolished sHZ‐induced IgG2c production, while recombinant IFN‐γ administration successfully rescued IgG2c CSR impairment in mice lacking B‐cell intrinsic MyD88. Together, our results show that B cell‐intrinsic MyD88 signaling is involved in the MOA of certain particulate adjuvants and this may enhance our specific understanding of how adjuvants and vaccines work. Abstract : Cell‐intrinsic MyD88 plays differential roles in the modes of action of vaccine adjuvants. Using synthetic hemozoin particulate adjuvant, we found that B cell intrinsic MyD88 is required for IFNγ induction in T cells, NK cells and dendritic cells to induce IgG2c class switching in a TLR/IL1‐independent manner.